Effect of educational intervention in reducing exposure to second hand tobacco smoke among 12-year-old children as determined by their salivary cotinine levels and knowledge, attitude and behavior - a randomized controlled trial - Rao, Ashwini; Rungta, Nikita; Nandini, M.; Unnikrishnan, B.; Shenoy, Ramya; Rao, Arathi; Shetty, Mranali K. (Frontiers in Oral Health, 2023)
Background: Tobacco use is one of the most important public health concerns, with approximately 8.7 million tobacco-related deaths each year, primarily in low-and middle-income countries. Even more concerning is the fact that 1.3 million of these deaths are seen in nonsmokers, including babies and children. This study was performed to determine whether a school-based 'tobacco-free' educational intervention program among 12-year-old children would be effective in reducing their exposure to second-hand tobacco smoke (SHS) by improving their knowledge, attitude and behavior post intervention and estimating salivary cotinine levels as markers of SHS exposure. Materials and method: A randomized controlled trial was performed by a cluster random sampling technique, with 30 participants each in the experimental and control arms. A knowledge, attitude, avoidance behavior and self-efficacy of avoidance questionnaire was administered, followed by estimation of salivary cotinine levels. The experimental arm received the 'tobacco-free' intervention, which comprised a 40minute health education session, with the first follow-up at 15 days and the second at 30 days after the intervention. After the intervention, the questionnaire was readministered, followed by re-estimation of salivary cotinine levels. Results: One month after the intervention, the number of participants who had a smoker who lived with them and the number of people who smoked inside the house were reduced in the experimental group compared to the control group. In the knowledge domain and the attitude domain, 80% and 60% of the items showed a statistically significant improvement in the experimental group compared to the control group. In the avoidance behavior domain and the Self-Efficacy of Avoidance Domain, all the items showed improvement in the experimental group compared to the control group. When the mean salivary cotinine levels were compared pre-and postintervention, it was found that although the mean postintervention salivary cotinine levels increased in both the This is a provisional file, not the final typeset article experimental and control groups, the increase was less in the experimental group than in the control group. Conclusion: The present study has been shown to be effective in improving the knowledge, attitude and avoidance behavior of adolescents toward exposure to secondhand smoke.